X-ray-structure of a cytidylyl-3',5'-adenosine-proflavine complex: a self-paired parallel-chain double helical dimer with an intercalated acridine dye. - Westhof, E (1980)
The non-self-complementary dinucleoside monophosphate cytidylyl-3',5'-adenosine (CpA) forms a base-paired parallel-chain dimer with an intercalated proflavine. The dimer complex possesses a right-handed helical twist. The dimer helix has an irregular girth with a neutral adenine-adenine (A-A) pair, hydrogen-bonded through the N6 and N7 sites (C1'...C1' separation of 10.97 A), and a triply hydrogen-bonded protonated cytosine-cytosine (C-C) pair with a proton shared between the base N3 sites (Cl'...Cl' separation of 9.59 A). The torsion angles of the sugar-phosphate backbone are within their most preferred ranges and the sugar puckering sequence (5' leads to 3') is C3'-endo, C2'-endo. There is also a second proflavine molecule sandwiched between CpA dimers on the 21-axis. Both proflavines are necessarily disordered, being on dyad axis, and this suggests possible insights into the dynamics of intercalation of planar drugs. This structure shows that intercalation of planar drugs in nucleic acids may not be restricted to antiparallel complementary Watson-Crick pairing regions and provides additional mechanisms for acridine mutagenesis.